Psychological symptoms among hospital nurses in Taiwan: a cross sectional study - Mei-Ju Chen; Shiue-Shan Weng (BMC, 2017)
Abstract Background A considerable number of studies have identified the risk factors attributable to job-related stress among nurses. However, studies investigating psychological symptoms among hospital nurses is still lacking, especially in Taiwan, where the average patient to nurse ratio is among the highest in the world. This study aimed to investigate the potential role of self-rated health status, self-reported diseases, and utilization of occupational health checks in psychological symptoms among Taiwanese nurses. Methods A cross-sectional design was conducted from September through December 2013. Data were collected through online self-administered questionnaire among 697 registered nurses in seven regional hospitals governed by the Taipei City Government. Results Nurses with fair or poor self-rated health, lower education, <30 years of age, and low back pain were more likely to suffer from psychological symptoms. A trend toward significance was also noticed for those aged 30-39. Importantly, low back pain was the most common disease among nurses in self-reported diseases and half of the nurses reported not utilizing the occupational health examination for the last 5 years. Conclusions To alleviate or prevent the psychological symptoms, psychosocial support, and awareness program on prevention of occupational injuries should be offered to nurses younger than 39 years old and having lower educational levels. Moreover, underutilization of occupational health examination among nurses deserves more attention.